(untitled) - Moule, Jean (Belmont, CA, 2012)
We all know that an appreciation of diversity is important, but how do you teach that to students? Cultural competence: A primer for educators, 2nd Edition, shows you the basics of multicultural education strategies in a short, easy-to-use education textbook. The author also offers insights into the psycho-social dimensions of teaching culturally diverse populations. Thorough yet concise, this is the guide you'll need to ensure that you emphasize the importance of diversity in your classroom.
Keywords: Multicultural education,Cultural competence,Giáo dục đa văn hóa,Thẩm quyền văn hóa; United States,United States,Hoa Kỳ,Hoa Kỳ